(untitled) (Eurasian Medical Research Periodical, 2023)
The purpose of this study is to study the features of the clinic and the course of acute otitis media in children with type 1 diabetes mellitus. It has been shown that in type 1 diabetes mellitus, children under 14 with acute otitis media account for 60 patients. Of these, 32 patients are boys, and 28 girls. As a result of the analysis of our data, it was found that the most common signs of acute otitis media in children are: ear pain, suppuration, fever, toxicosis, exsicosis. The peculiarity of the clinical manifestation of acute otitis media in children, in our opinion, is primarily associated with both the biological properties of the underlying disease (damage to immunocomponent cells) and the anatomical and physiological characteristics of the child’s body. Summarizing, it should be noted that the clinic and the course of acute otitis media in children with DM are similar to those in children who do not have diabetes mellitus, that is, when choosing antibiotic therapy, doctors should follow the same recommendations as in the treatment of acute otitis media in immunocomponent children